The Role of the World Wide Fund for Nature (WWF) Hong Kong in the Conservation of Mai Po in 2013–2018 - Silvia Nurhaliza Farida (Universitas Ibn Khaldun, 2026)
This study examines the role of the World Wide Fund for Nature (WWF) Hong Kong in the conservation of the Mai Po wetland area during the period of 2013–2018. Mai Po, part of the East Asian–Australasian Flyway and designated as a Ramsar site, faces significant threats from urbanization, climate change, and habitat degradation. WWF Hong Kong implemented an integrated, science-based, and participatory conservation approach, including adaptive habitat management, environmental education, community empowerment, and public policy advocacy. Through programs such as Wetland School, Nature with No Barriers, and Walk for Nature, WWF successfully raised public awareness and participation in environmental conservation. In addition, WWF played a key role as a facilitator of international cooperation for migratory bird conservation across East Asia. The study reveals that WWF’s success lies not only in the technical management of ecosystems but also in its ability to build cross-sectoral partnerships for sustainable conservation. These findings provide valuable lessons for similar conservation efforts in other regions facing comparable challenges.